2018
DOI: 10.1155/2018/4302607
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Fiber-Reinforced Composites for the Coronoradicular Reconstruction of Premolar Teeth: A Finite Element Analysis

Abstract: A coronoradicular reconstruction (CRR) has conventionally used a metallic inlay core (MIC) or a single-fiber-reinforced composite (sFRC) but extensive dentin removal can lead to root fracture. We propose herein a multi-fiber-reinforced composite (mFRC) based on a bundle of thin flexible fibers that can be adapted to the root anatomy without removing additional dentin. The aim of this study was to compare the mechanical behavior of the root reconstructed with mFRC, MIC, or sFRC using a finite element analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…However, other failure criteria that neglect plasticity could have been used, such as the maximum principal stress [ 13 ], which could have changed the results of the DOE. Furthermore, the development of adhesive dentistry and more conservative fiber posts has considerably changed the tooth restoration, and further investigations now appear to be required to evaluate the influence of these new strategies on EMS [ 29 , 30 ]. Moreover, EMS also aims to treat persisting apical periodontitis due to extra-radicular infection without the presence of a post.…”
Section: Discussionmentioning
confidence: 99%
“…However, other failure criteria that neglect plasticity could have been used, such as the maximum principal stress [ 13 ], which could have changed the results of the DOE. Furthermore, the development of adhesive dentistry and more conservative fiber posts has considerably changed the tooth restoration, and further investigations now appear to be required to evaluate the influence of these new strategies on EMS [ 29 , 30 ]. Moreover, EMS also aims to treat persisting apical periodontitis due to extra-radicular infection without the presence of a post.…”
Section: Discussionmentioning
confidence: 99%
“…The application of mFRC into the root canal space does not require any use of post-space preparation [ 27 ]. Therefore, the adhesive area between mFRC and root canal dentin could be smaller than the adhesive area between sFRC and root canal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the placement of sFRC posts often implies extensive removal of the root dentin, which is a major drawback, since tissue preservation is strongly associated with the survival of endodontically treated teeth [ 25 , 26 ]. Several studies [ 27 , 28 ] showed an alternative type of FRC. That is a multi-fiber-reinforced composite (mFRC) based on a bundle of fibers that are bonded directly to the root canal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the loss of dental hard substance resulting from root canal preparation, the different mechanical properties of the posts compared to the tooth properties can cause a decrease in tooth strength [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%